Complete plastid genome of Persea americana Mill. (Ebenales) and phylogenetic analysis - Jin Liu; Li-Dan Gong; Lin Qi; Cheng Zheng; Ying-Feng Niu; Chao Shi (Mitochondrial DNA. Part B. Resources, 2019)
The chloroplast (cp) genome sequence of Persea americana Mill. has been characterized from Illumina pair-end sequencing. The complete cp genome was 152,732 bp in length, containing a large single copy region (LSC) of 84,632 bp and a small single copy region (SSC) of 18,346 bp, which were separated by a pair of 24,877 bp inverted repeat regions (IRs). The genome contained 126 genes, including 86 protein coding genes, 32 tRNA genes, and eight rRNA genes. Further, phylogenetic analysis of 10 representative sequences within the order Ebenales suggests that Persea americana Mill. is closely related to the species in family Sapotaceae.